IN THE BORDERS OF CHRISTIANITY: the missions as bastions of European empires in Africa - Stephanie Caroline Boechat Correia (Clio: Revista de Pesquisa Histórica, 2012)
The missions accounted for Christianity the same as the armies for the kings. They constitute the necessary support, in the spiritual field, to the achievements and to the lands that were only political and trading allies of European kings. It was through the missions that the Holy See could expand the word of Christ within and outside the old continent. In the kingdom of Congo, the Catholic missionaries had to deal with what they call african "idolatry", sometimes with open confrontation, either with silence and acceptance. In the first half of the seventeenth century, they had to deal with several threats, including Calvinism brought by the Dutch that anchored in ports of Congo.